1993
DOI: 10.1002/jcp.1041550118
|View full text |Cite
|
Sign up to set email alerts
|

Proteases are implicated in the changes in the Sertoli cell cytoskeleton elicited by follicle‐stimulating hormone or by dibutyryl cyclic AMP

Abstract: Follicle-stimulating hormone (FSH) or dibutyryl cyclic AMP (dbcAMP) elicits striking morphological changes in Sertoli cells in culture in serum-free medium, resulting in a transition from an epithelial type of cell association pattern to that of an astrocytic or fibroblast-like cell, with attenuated cytoplasmic extensions between cells, and with diminished F-actin stained stress fibers. These responses of Sertoli cells do not occur in the presence of normal untreated serum, but they do take place in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The C-terminal fragment of FLNA then bound to the AR in a ligand-independent manner, repressed AR-mediated transactivation (more than full-length), and was required for AR nuclear translocation (Ozanne et al, 2000;Loy et al, 2003). In addition, it was previously shown that the general protease inhibitor a 2 -macroglobulin prevented the cAMP-mediated reorganization of the Sertoli cell actin cytoskeleton (Tung et al, 1993). So perhaps the most important aspect of Palld expression and regulation in the testis is not which isoform is transcribed, but where and how the protein is cleaved by specific proteases.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal fragment of FLNA then bound to the AR in a ligand-independent manner, repressed AR-mediated transactivation (more than full-length), and was required for AR nuclear translocation (Ozanne et al, 2000;Loy et al, 2003). In addition, it was previously shown that the general protease inhibitor a 2 -macroglobulin prevented the cAMP-mediated reorganization of the Sertoli cell actin cytoskeleton (Tung et al, 1993). So perhaps the most important aspect of Palld expression and regulation in the testis is not which isoform is transcribed, but where and how the protein is cleaved by specific proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that Sertoli cells, the primary supportive cells of the seminiferous epithelium, play a key role in triggering and regulating spermatogenesis (de Kretser et al, 1998) and have a well‐developed cytoskeleton that is responsible for the formation of the seminiferous epithelium and the development of germ cells (Boekelheide et al, 1989; Russell et al, 1989; Muffly et al, 1993; Tung et al, 1993). Morphologic studies have implicated the Sertoli cytoskeleton in the maintenance of cell shape, localization and transformation of cytoplasmic organoids, formation and stabilization of cell‐cell or cell‐extracellular matrix contacts, localization, anchoring and migration of developed germ cells, and the release of mature sperm from seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue remodeling process and the production of Sertoli cell factors leads to the constitution of a specific biochemical and cytoarchitectural microenvironment in the adluminal compartment, in which germ cells will proliferate and differentiate. Sertoli cell products include binding and transport proteins (Han et al, 1993), extracellular matrix and junctional proteins (Dym and Fawcett, 1970, 1971; Russell and Peterson, 1985; Han et al, 1993; Chen and Mruk, 2002), proteases and protease inhibitors (Tang et al, 1993), growth factors (Gnessi et al, 1997), and energy substrates such as lactate (Grootegoed and Den Boer, 1990). However, there is no available information on the mechanism of vitamin C transport across the blood–testis barrier.…”
mentioning
confidence: 99%